Food Evaluation Regarding the Safety Market of Dairy Products in Braila County, Romania - Violeta Gagu (Leoca); Constanta Laura Zugravu; Gheorghe Adrian Zugravu (Journal of Agriculture and Rural Development Studies)
This assessment focuses on the safety of the dairy products market in Romania, according to data provided by the National Authority for Consumer Protection (ANPC). The review covers a wide range of dairy products, including milk, cheeses, yoghurts and butter, with the aim of identifying potential risks to public health. The study used ANPC data collected from inspections and quality controls. The National Authority for Consumer Protection (ANPC) is focused on a number of specific areas, especially aiming at the continuation and strengthening of the process of European legislative harmonization, cooperation and regulation, information, education and advice of consumers and traders, control and supervision of market, as well as specific activities in the field of precious metals and stones.